Toxicity of Tire Rubber Microplastics to Freshwater Sediment Organisms - Carrasco-Navarro, Victor; Nuutinen, Aino; Sorvari, Jouni; Kukkonen, Jussi V. K. (Springer, 2021)
High emission of tire rubber particles to the surrounding environment is an inevitable consequence of the current habits of transportation. Although most of the emissions stay within a close range of the sources, it has been proven that the smallest particles can be transported to remote locations through the atmosphere, including inland water bodies. It has been estimated that a relevant portion of the global emissions of tire rubber particles reach surface waters, but effects on aquatic life in the receiving water bodies are not completely understood. In the present study, we used the freshwater sediment dwellers Lumbriculus variegatus and Chironomus riparius to examine the toxicity of tire rubber particles at environmentally relevant concentrations, using different types of sediment and two particle sizes of tire rubber. Overall, the experiments were unable to discern any effects on the growth, survival or reproduction of the two animals tested. Significant differences were found among the animals dwelling on different sediments, but the effects were not attributable to the presence of tire rubber particles. This study provides important information regarding the lack of effect of tire rubber particles in laboratory experiments with model sediment dwellers and opens more questions about the potential effects of tire rubber particles in the real environment with longer durations and varying environmental factors. The influence of other factors such as the leaching of additives in the overall toxicity of tire rubber particles should be also considered.
Keywords: tire rubber particles; freshwater sediment dwellers; toxicity